2017
DOI: 10.1080/01635581.2017.1359320
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Obesity on the Regulation of Macrophage Population in the Prostate Tumor Microenvironment

Abstract: Obesity is associated with a greater risk of prostate cancer mortality. However, the mechanisms connecting obesity to the progression of prostate cancer remain unknown. This study determined the impact of obesity on macrophage recruitment and tumor-associated macrophage (TAM) polarization in the prostate tumor microenvironment, since a high concentration of TAMs in tumors has been linked to progression in prostate cancer. We utilized an in vitro model in which pre-adipocytes, prostate cancer cells, and macroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…In vitro, macrophages coming from obese subjects or exposed to conditions mimicking the obese microenvironment showed increases in migration and upregulation of markers of TAM. In the same study, it was also demonstrated that obesity promoted macrophages infiltration in the prostate tumor microenvironment, and induced TAM polarization through the COX2-PGE2 pathway 155 .…”
Section: Obesity and Pregnancymentioning
confidence: 85%
“…In vitro, macrophages coming from obese subjects or exposed to conditions mimicking the obese microenvironment showed increases in migration and upregulation of markers of TAM. In the same study, it was also demonstrated that obesity promoted macrophages infiltration in the prostate tumor microenvironment, and induced TAM polarization through the COX2-PGE2 pathway 155 .…”
Section: Obesity and Pregnancymentioning
confidence: 85%
“…Among these risk factors, obesity is associated with the development of kidney and PCs . A recent in vitro study regarding PC showed that obesity promotes macrophage infiltration into the prostate tumor microenvironment, inducing tumor‐associated macrophage polarization through the COX‐2/PGE2 pathway . In contrast, cancer cells per se elicit inflammation by recruitment and activation of inflammatory cells in the tumor microenvironment …”
Section: Introductionmentioning
confidence: 99%
“…2 A recent in vitro study regarding PC showed that obesity promotes macrophage infiltration into the prostate tumor microenvironment, inducing tumor-associated macrophage polarization through the COX-2/PGE2 pathway. 3 In contrast, cancer cells per se elicit inflammation by recruitment and activation of inflammatory cells in the tumor microenvironment. 4 In the urological cancer research field, several studies have shown an association among infiltration of inflammatory cells, such as neutrophils and macrophages, tumor aggressiveness, and poor prognosis.…”
mentioning
confidence: 99%
“…CCL2 is one of the key chemokines involved in attracting monocytes and macrophages, and it has been found to circulate at higher levels in obesity. Moreover, adipose cells are major contributors to CCL2 levels [30,31], and expression of CCL2 along with numbers of macrophages increases in the prostate cancer tissue of obese mice [32]. In this study, CCL2 produced from adipocyte activated by TCM attracted macrophages more strongly than ACM, which contained less CCL2 (Fig.…”
Section: Discussionmentioning
confidence: 52%